Hints on the origin of the thermal hysteresis suppression in giant magnetocaloric thin films irradiatied with highly charged ions. (November 2015) - Cervera, S; Trassinelli, M; Marangolo, M; Carlsson, L Bernard; Eddrief, M; Etgens, V H; Gafton, V; Hidki, S; Lamour, E; Lévy, A; Macé, S; Prigent, C; et al.
Abstract: In a recent experiment we demonstrated the possibility to suppress the thermal hysteresis of the phase transition in giant magnetocaloric MnAs thin film by interaction with slow highly charged ions (Ne 9+ at 90 keV) [1]. This phenomenon has a major impact for possible applications in magnetic refrigeration and thus its reproducibility and robustness are of prime importance. Here we present some new investigations about the origin and the nature of the irradiation-induced defects responsible for the thermal hysteresis suppression. Considering in particular two samples that receive different ion fluences (two order of magnitude of difference), we investigate the reliability of this process. The stability of the irradiation-induced defects with respect to a soft annealing is studied by X-ray diffraction and magnetometry measurements, which provide some new insights on the mechanisms involved.